A methodology for flexibility analysis of pipeline systems - Zahid, Umer; Khan, Sohaib Z.; Khan, Muhammad A.; Bukhari, Hassan J.; Nisar, Salman; Khan, Kamran Ahmed (SAGE, 2018)
Pipeline systems serve a crucial role in an effective transport of fluids to the designated location for medium to long span of distances. Owing to its paramount economic significance, pipeline design field have undergone extensive development over the past few years for enhancing the optimization and transport efficiency. This research paper attempts to propose a methodology for flexibility analysis of pipeline systems through employing contemporary computational tools and practices. A methodical procedure is developed, which involves modeling of the selected pipeline system in CAESAR II followed by the insertion of pipe supports and restraints. The specific location and selection of the inserted supports is based on the results derived from the displacement, stress, reaction, and nozzle analysis of the concerned pipeline system. Emphasis is laid on the compliance of the design features to the leading code of pipeline transportation systems for liquid and slurries, ASME B31.4. The discussed procedure and approach can be successfully adjusted for the analysis of various other types of pipeline system configuration. In addition to the provision of systematic flow in analysis, the method also improves efficient time-saving practices in the pipeline stress analysis.
Keywords: Pipeline; flexibility analysis; CAESAR II; ASME B31.4